2000
DOI: 10.1093/ps/79.11.1557
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the contribution of water activity and moisture content to the population distribution of Salmonella spp. in commercial poultry houses

Abstract: Because Salmonella spp. can be spread from the production environment to the consumer, strategies are required to control Salmonella. One such intervention involves control of the distribution of the organism in poultry litter. In this regard, we have attempted to determine whether Salmonella spp. are uniformly distributed throughout the litter of commercial poultry houses, or if they are unevenly localized to "hot spots" associated with high surface litter water activity (Aw) and high total moisture levels. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…(Bernhart and Fasina, 2009;Carr et al, 1995;Eriksson De Rezende et al, 2001;Hayes et al, 2000). We suggest that differences observed between studies may be due to differences in the bedding materials, A w testing conditions (e.g.…”
Section: A B Rmentioning
confidence: 85%
See 2 more Smart Citations
“…(Bernhart and Fasina, 2009;Carr et al, 1995;Eriksson De Rezende et al, 2001;Hayes et al, 2000). We suggest that differences observed between studies may be due to differences in the bedding materials, A w testing conditions (e.g.…”
Section: A B Rmentioning
confidence: 85%
“…It has previously been recommended that the A w of poultry litter should be kept below 0.84e0.91 to restrict the growth of Salmonella and other microbiota (Chinivasagam et al, 2012;Eriksson De Rezende et al, 2001;Hayes et al, 2000;Payne et al, 2007). Carr et al (1994) reported that new bedding material (sawdust) had higher A w than litter and this was associated with the presence of Salmonella.…”
Section: Effect Of a W On Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Samples consisted of either poultry litter or swabs of poultry transport containers. Surface poultry litter was collected from 55 roaster and broiler chicken houses located on the eastern seaboard of the United States, as described previously (16). Over a period of 11 weeks in the summer of 1998, two swabs from each of 103 poultry transport containers representing 27 farms were periodically collected at a regional processing facility.…”
Section: Methodsmentioning
confidence: 99%
“…Although we found no correlation between dry matter content of the litter and Salmonella spp. concentration in the litter as described by Hayes et al (2000); when litter is dry it is more prone to becoming airborne as a consequence of increased ventilation rate or birds movement . In fact, we found strong correlations between airborne Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%